Psychological safety as a context-sensitive predictor of retention intentions: Gendered effects of supervisor support under caregiving-assumed conditions - Michi Yoshimura; Hiroyuki Yamaguchi (PLoS ONE, 2026)
This study examined how emotional and instrumental supervisor support influence employees’ retention intentions through psychological safety, with a particular focus on gender and caregiving contexts. An online questionnaire survey was conducted among 522 Japanese employees (248 men and 274 women), and the hypothesized model was tested using structural equation modeling (SEM), multi-group invariance analysis, and bootstrapping. The analysis revealed clear differences in the indirect effects of emotional support on retention intentions via psychological safety between the general working condition and the caregiving-assumed condition. Under the general condition, the indirect effects were statistically significant for both men and women; however, the standardized indirect effects ( β ) were small in magnitude, particularly among men. In contrast, when employees assumed future caregiving responsibilities, the magnitude of the mediated pathway increased substantially, and the influence transmitted through psychological safety became markedly stronger. Furthermore, the direct effect of psychological safety on retention intentions also exhibited context-dependent variation. Among men, this direct path was non-significant under the general condition but became significantly and markedly stronger under the caregiving-assumed condition. Among women, the direct effect was significant under both conditions but was notably stronger when caregiving responsibilities were assumed. In contrast, instrumental support did not show significant effects under either condition, suggesting that practical assistance alone may be insufficient to enhance psychological safety or retention intentions when interpersonal risk is salient. Taken together, these findings suggest that when employees anticipate future caregiving burdens, the strength of the influence transmitted through psychological safety increases, indicating that the effectiveness of emotional support varies considerably depending on contextual demands. These findings highlight the importance of psychological safety as a context-sensitive mechanism linking supervisor support to retention intentions, particularly under anticipated caregiving conditions.